Oil-immersed transformer temperature monitoring by ANSI/IEEE C57.91 model - Maleewat, P.; Tadsuan, S.; Saelee, V.; Chompoo-inwai, C. (My University, 2007)
This article presents the development of a 3-phase oil immersed transformer temperature monitoring equipment. The developing prototype employs ANSI/IEEE C57.91 standard mathematical model to calculate the hottest spot of the transformer winding, and use the AT89CS8252 MCS51 microcontroller for an implementation. Main components of the newly developed prototype consists of input sensors, MCS51 microcontroller, and 7-segment display. Input sensors are RTD (PT100), CT and PT. An output display is 7-segment displaying transformer current, voltage, ambient temperature, top-oil temperature and hot-spot temperature. Test results show that measuring temperatures obtained from the new prototype are close to those from the conventional standard measuring instruments (CSI). As a result, transformer industries can find the benefits of the developing prototype of gathering and analysis transformer temperature data. In addition, this equipment can notify operators if their operating transformers are withstanding the overload or over temperature or not. © 2007 RPS.
Keywords: Hot-spot temperature; Oil-immersed transformer; Top-oil temperature